Pengaruh Capital Structure, Activity Ratio, Sales Growth, Firm Size, Dan Inflasi Terhadap Financial Distress Pada Perusahaan Sector Technology Yang Terdaftar Di BEI Periode 2021 - 2024 - Syifa Aulia Mahadevi; Ulil Hartono; Nadia Asandimitra Haryono (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study examines the effect of capital structure, activity ratio, sales growth, firm size, and inflation on financial distress in technology sector companies listed on the Indonesia Stock Exchange during 2021-2024. The research uses a causal quantitative design with secondary data from annual reports, financial statements, and official inflation data. Financial distress is measured using the Springate S-Score and converted into a dummy variable, where 1 indicates distress and 0 indicates non-distress. Using purposive sampling, 28 companies were selected from 47 technology firms, producing 112 firm-year observations. The data were analyzed using binary logistic regression with Stata 17. The results show that 42 observations or 37.5% were classified as distressed. The model passed the Hosmer-Lemeshow test, achieved 78.57% classification accuracy, and produced an AUC of 0.8565. Activity ratio, firm size, and inflation have a significant negative effect on financial distress, while capital structure and sales growth are not significant. The findings indicate that asset efficiency and company scale are more decisive in reducing financial distress risk than debt structure or sales expansion alone.